2017
DOI: 10.1093/abbs/gmw139
|View full text |Cite
|
Sign up to set email alerts
|

Salubrinal protects against toxin B-induced CT26 cell death

Abstract: Clostridium difficile (C. difficile) is considered to be the major cause of the antibiotic-associated diarrhea and pseudomembranous colitis in animals and humans. The prevalence of C. difficile infections (CDI) has been increasing since 2000. Two exotoxins of C. difficile, Toxin A (TcdA) and Toxin B (TcdB), are the main virulence factors of CDI, which can induce glucosylation of Rho GTPases in host cytosol, leading to cell morphological changes, cell apoptosis, and cell death. The mechanism of TcdB-induced cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
2
6
0
Order By: Relevance
“…It also demonstrated that it could offer neuroprotection through UPR-related signaling factors along with other biochemical events [8]. e concentrations of Sal utilized in different organs or tissues showed varying difference [27][28][29]. In the present study, we have observed that the viability of the ACC cells was inhibited by Sal at the given dose.…”
Section: Discussionsupporting
confidence: 49%
“…It also demonstrated that it could offer neuroprotection through UPR-related signaling factors along with other biochemical events [8]. e concentrations of Sal utilized in different organs or tissues showed varying difference [27][28][29]. In the present study, we have observed that the viability of the ACC cells was inhibited by Sal at the given dose.…”
Section: Discussionsupporting
confidence: 49%
“…Our previous study indicated that salubrinal inhibited migration and adhesion of osteoclast in a disuse osteoporosis animal model 10 . The previous study also demonstrated that salubrinal prevented the glycosylation of Rac1 caused by eIF2α signaling pathway 60 . Based on the result with eIF2α siRNA, this downregulation was in part mediated by eIF2α signaling.…”
Section: Discussionmentioning
confidence: 85%
“…Usually it was thought that the enzyme hosted in a RM could display its highest activity when the size of the inner cavity of the RMs matched the size of the enzyme, which means that the size of the free water core should be either bigger than the enzyme or equal at least. [12] In some research, higher enzyme activity obtained in the bigger aqueous cores of the RMs than those in the smaller ones was reported. [20] The RM size is linearly proportional to the ratio ω 0 when it is above the value needed for hydration of the surfactant polar headgroups, under the hypothesis that the RMs are considered as simple spherical geometry and assuming that all the surfactants are aggregated in a micelle form.…”
Section: Water Solubilizationmentioning
confidence: 99%
“…It is probably because the small size of aqueous core of RMs alters the formation of the enzyme active sites, which are produced by folding the long and linear chain of the amino acids. [12] However, even under this situation, RL showed its excellent ability in terms of solubilizing more water, building bigger aqueous core and forming more stable RMs. As we can see from the graph, the degradation rate is obviously higher than the other systems, and by around 20% higher than in the AOT-based RMs.…”
Section: (A) Shows the O-h Stretching Bands Of Watermentioning
confidence: 99%
See 1 more Smart Citation